Sosialisasi Pencegahan Stunting di Desa Ridogalih - Dihak Maulana Nur A; Dita Nursafitri; Kemal Fiqri Handoko; Luthfiyya Junia Sumantri; Marinus Halawa (Universitas Nusa Putra & Persatuan Insinyur Indonesia, 2024)
Stunting poses a serious health challenge affecting child growth. This study evaluates the effectiveness of stunting prevention socialization in Ridogalih Village, emphasizing the promotion of a healthy lifestyle. Through educational activities and distributing informative materials, the community gains an understanding of balanced nutrition, sanitation, and proper childcare. Pre- and post-socialization surveys measure changes in knowledge and community actions related to a healthy lifestyle as a stunting prevention strategy. Results show improved understanding and implementation of a healthy lifestyle. However, sustained efforts are needed to reinforce behavioral changes toward a lifestyle supportive of optimal child growth. This study contributes to enhancing awareness and community participation in stunting prevention by focusing on a healthy lifestyle, thereby supporting the well-being of children and future generations in Ridogalih Village.